Meningkatkan Ketakwaan Dan Hasil Belajar PAK Dengan Metode PBL Kelas V SD Santo Yusup Cimahi - Tatik Sugiharti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The purpose of this research is to increase piety and learning outcomes with the PBL (Problem Based Learning) method. The methods used were initial assessment, cognitive assessment, and observation with reference to KKTP (Learning Objective Completeness Criteria). The subjects were students of phase C Class 5 AY SD Santo Yusup Cimahi. The piety aspect was examined through observation in the rubric of the Learning Objectives Completeness Criteria (KKTP) instrument using the PBL method. Based on the analysis of the results of the piety research, students are getting bolder and more consistent in voicing the truth about men and women. The increase in class average scores from cycle I to cycle II increased by 5.2%, from 65 to 100. The average score in cycle II for the very high score category of students increased by 20.2%, from 18 students to 27 students. Student learning outcomes achieve an indicator of success from the Learning Objectives Completeness Criteria (KKTP) of 90% percent.